Optimalisasi Perawatan Sekoci Penolong dan Dewi-Dewi Sebagai Penunjang Keselamatan Pelayaran di KM. Kendhaga Nusantara 6 - Muhammad Alfin Prasetiya; Ari Sriantini; Dedy Kristiawan (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2024)
Maintenance of the lifeboats and goddesses needs to be carried out so that they are ready for use by the lifeboats and goddesses at KM. Kendhaga Nusantara 6 when it was going to be used for training experienced traffic jams. Therefore, pilot 3 and engineer 3 carried out checks and maintenance of lifeboats once a week and lifeboat training was carried out once a month. This research aims to determine the implementation of lifeboat maintenance and goddesses, to find out the obstacles encountered in the implementation of maintenance of lifeboats and goddesses, as well as to find out efforts to overcome obstacles in the implementation of maintenance of lifeboats and goddesses. This research is of a quantitative type with a descriptive statistical approach, with the data collection method being interviews , observation, questionnaire. Before the questionnaire instrument was used, a validity and reliability test was carried out and the results were valid and reliable with a Cronbach's alpha value of 0.848. The results of this study showed that maintenance was not carried out according to schedule. Lifeboat maintenance was only carried out within 3 months within 1 year. Based on the results Questionnaires from 8 respondents consisting of master, master 1, mate 3, kkm, machinist 3, helmsman, boss, class, obtained the results that the percentage of lifeboat maintenance implementation was 51.6%, which means that the criteria were sufficient and the implementation of the goddess goddess was 50%, which meaning that the criteria are sufficient. From the results of this research it can be concluded that the optimal level of lifeboats and goddesses must be increased in maintenance according to procedures. The obstacle encountered was that during the exercise there was a jam on the lifeboat boats which resulted in the lifeboat not being able to be lowered and damage to the lifeboat engine. Efforts that must be made are to carry out maintenance according to the 1974 SOLAS procedure.